12: The Weight of Place – The Role of the Neighbourhood in Childhood Obesity. Issue 6 (1st June 2014) - Morinis, J; Lebovic, G; Gozdyra, P; Khovratovich, M; Carsley, S; Creatore, M; Moheddin, R; Booth, G; Maguire, J; Parkin, P; Glazier, R; Birken, C
Abstract: BACKGROUND: The neighbourhood environment provides both a social and physical context that is thought to have an effect on behaviours that may influence weight gain. There is limited research in this area on pre-school children. OBJECTIVES: The objective of this study is to examine the association between the built environment and body mass index (BMI) among pre-school-age children while adjusting for known individual level factors associated with pre-school obesity. DESIGN/METHODS: A cross sectional study of children one to five years of age was conducted using individual level data from the TARGet Kids! cohort in Toronto, Canada which includes prospectively collected data from 3928 children between September 2008 and June 2012. We characterized a child's neighbourhood using a validated neighbourhood walkability index based on 1) car ownership; 2) population per square kilometer of residential area; 3) all services per 10, 000 population; 4) average distance from residential points to nearest five retail locations; 5) crime per 100, 000).The main outcome was child's zBMI. RESULTS: The mean age of participants at baseline was 33.5 months. The proportion of children included in TARGetKids! with zBMI >1 (overweight) was 20.5% and zBMI >2 (obese) was 4.8%. The outcome, zBMI, was adjusted for: gender, ethnicity, age of child, birth weight, parental BMI, mother's education, free play outdoors, immigration status and neighbourhood level income. The mean zBMI decreased as the walkability of the neighbourhood increased. Compared to the most walkable neighbourhood, the average zBMI of the least walkable was 0.269 vs 0.063 in the most walkable neighbourhood in Toronto. This relationship was maintained after adjustment for individual level factors. CONCLUSIONS: Living in a walkable neighbourhood was associated with lower zBMI among preschool-age children after adjustment for individual level factors known to be associated with obesity in young children. Identifying modifiable built environment features that could mitigate the epidemic of childhood obesity could have population wide impact on the health of our children and the adults that they subsequently become.